Advanced antenna array engineering for 6G and beyond wireless communications - Guo, Y. Jay; Ziolkowski, Richard W. (Hoboken, New Jersey : Wiley-IEEE Press, 2022)
"Whilst 5G standards are in solid shape, the telecommunications industry faces tremendous engineering challenges in designing and deploying antennas which will not only deliver the expected 5G performance, but also can be installed in collocation with 4G antennas. It is expected that analogue antenna arrays will play a major part in enabling the cost-effective roll-out of 5G networks. Moreover, it is expected many 6G antennas will be mounted on airborne and spaceborne platforms. The nature of such space, air, and terrestrial integrated communications networks poses new challenges and demands for antennas with characteristics such as high gain, individually scannable multi-beams, immunity to interference, reconfigurability, and conformability to all platforms."--
Author Biographies -- Acknowledgements -- -- Chapter 1 A Perspective of Antennas for 5G and 6G -- 1.1 5G Requirements of Antenna Arrays -- 1.2 6G and Its Antenna Requirements -- 1.3 From Digital to Hybrid Multiple Beamforming -- 1.4 Analog Multiple Beamforming -- 1.5 Millimeter-Wave Antennas -- 1.6 THz Antennas -- 1.7 Lens Antennas -- 1.8 SIMO and MIMO Multi-beam Antennas -- 1.9 In-Band Full Duplex Antennas -- 1.10 Conclusions -- -- Chapter 2 Millimeter-Wave Beam Forming Networks -- 1. Circuit-Type BFNs: SIW Based Bulter and Nolen Matrixes -- 2. Quasi Optical BFNs: Rotman Lens and Reflectors -- 3. Conclusions -- -- Chapter 3 Decoupling Methods for Antenna Arrays -- 3.1. Electromagnetic Band-gap Structures -- 3.2. Defected Ground Structures -- 3.3 Neutralization Lines -- 3.4. Array-Antenna Decoupling Surfaces -- 3.5 Metamaterial Structures -- 3.6 Parasitic Resonators -- 3.7 Conclusions -- -- Chapter 4 De-scattering Methods for Coexistent Antenna Arrays -- 4.1 De-scattering vs Decoupling in Coexistent Antenna Arrays -- 4.2 Mantle Cloak De-Scattering -- 4.3 Lumped-Choke De-Scattering -- 4.4 Distributed-Choke De-Scattering -- 4.5 Mitigating the Effect of HB Antennas on LB Antennas -- 4.6 Conclusions -- -- Chapter 5 Differentially-fed Antenna Arrays -- 5.1 Differential Systems -- 5.2 Differential-fed Antenna Elements -- 5.3 Differential-fed Antenna Arrays -- 5.4 Differential-fed Multi-Beam Antennas -- 5.5 Conclusions -- -- Chapter 6 Conformal Transmitarrays -- 6.1 Conformal Transmitarrays Challenges -- 6.2 Conformal Transmitarrays Employing Triple-Layer Elements -- 6.3 Beam Scanning Conformal Transmitarrays -- 6.4 Conformal Transmitarray Employing Ultra-thin Dual-Layer Huygens Elements -- 6.5 Elliptically Conformal Multibeam Transmitarray with Wide-Angle Scanning Ability -- 6.6 Conclusions -- -- Chapter 7 Frequency Independent Beam Scanning Leaky Wave Antennas -- 7.1 Reconfigurable Fabry-Pérot (FP) LWA -- 7.2 Period-Reconfigurable SIW Based LWA -- 7.3 Reconfigurable Composite Right/Left-Handed LWA -- 7.4 Two Dimensional Multibeam Leaky Wave Antenna -- 7.5 Conclusions -- -- Chapter 8 Beam Pattern Synthesis of Analogue Arrays -- 8.1 Thinned Antenna Arrays -- 8.2 Arrays with Rotated Elements -- 8.3 Arrays with Tracking Abilities Employing Sum and Difference Patterns -- 8.4 Synthesis of SIMO Arrays 8.5 Conclusions
Includes index
BIBINDX
Keywords: Antenna arrays; Wireless communication systems; Electronic books